Sugar and acid profile of loquat (Eriobotrya japonica Lindl.), enzymes assay and expression profiling of their metabolism-related genes as influenced by exogenously applied boron - Ali, Muhammad Moaaz; Anwar, Raheel; Rehman, Rana Naveed Ur; Ejaz, Shaghef; Ali, Sajid; Yousef, Ahmed F.; Ercisli, Sezai; Hu, Xiaobo; Hou, Youming; Chen, Faxing (Frontiers in Plant Science, 2022)
Soluble sugars and organic acids are the most abundant components in ripe fruits, and they play critical roles in the development of fruit flavor and taste. Some loquat cultivars have high acid content which seriously affect the quality of fruit and reduce the value of commodity. Consequently, studying the physiological mechanism of sugar-acid metabolism in loquat can clarify the mechanism of their formation, accumulation and degradation in the fruit. Minerals application has been reported as a promising way to improve sugar-acid balance of the fruits. In this study, loquat trees were foliar sprayed with 0.1, 0.2 and 0.3% borax, and changes in soluble sugars and organic acids were recorded. The contents of soluble sugars and organic acids were determined using HPLC-RID and UPLC-MS, respectively. The activities of enzymes responsible for the metabolism of sugars and acids were quantified and expressions of related genes were determined using quantitative real-time PCR. The results revealed that 0.2% borax was a promising treatment among other B applications for the increased levels of soluble sugars and decreased acid contents in loquats. Correlation analysis showed that the enzymes i.e., SPS, SS, FK, and HK were may be involved in the regulation of fructose and glucose metabolism in the fruit pulp of loquat. While the activity of NADP-ME showed negative and NAD-MDH showed a positive correlation with malic acid content. Meanwhile, EjSPS1, EjSPS3, EjSS3, EjHK1, EjHK3, EjFK1, EjFK2, EjFK5, and EjFK6 may play an important role in soluble sugars metabolism in fruit pulp of loquat. Similarly, EjPEPC2, EjPEPC3, EjNAD-ME1, EjNAD-MDH1, EjNAD-MDH5-8, EjNAD-MDH10, and EjNAD-MDH13 may have a vital contribution to malic acid biosynthesis in loquat fruits. This study provides new insights for future elucidation of key mechanisms regulating soluble sugars and malic acid biosynthesis in loquats.